Analisis Pengaruh Good Corporate Governance, Ukuran Perusahaan, Dan Leverage Perusahaan Terhadap Kinerja Keuangan (Studi Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022) - Putri, Risnaini Kurnia; Mulyati, Henny (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of good corporate governance, company size and leverage on financial performance. Financial performance. The object of this research is food and beverage companies in the 2018-2022 period listed on the Indonesia Stock Exchange. Period 2018-2022 which are listed on the Indonesia Stock Exchange. Mechanism of good .Corporate governance mechanism is proxied by the board of commissioners and independent commissioners, company size as measured by total assets, and leverage as measured by total assets. Independent commissioners, company size as measured by total assets, and leverage as measured by Debt to Equity Ratio (DER). Measured by Debt to Equity Ratio (DER) and financial performance measured by Return On Asset (ROA). With Return On Asset (ROA). This type of research is quantitative research. Associative research. The sample used in this study was obtained using. Using purposive sampling method based on predetermined criteria, namely from food and beverage companies. Criteria, namely from food and beverage companies with a population of 15 companies. Company. The number of samples in this study was 75. Method used in this study is multiple linear regression analysis using the SPSS version 26 program. Using the SPSS version 26 program. The results showed that. The board of commissioners variable has a positive and significant effect on financial performance, the independent commissioner variable has a positive and significant effect on financial performance. Financial performance, the independent commissioner variable has a positive and significant influence on financial performance, the company size variable has a positive and significant influence on financial performance. On financial performance, the company size variable has a negative and insignificant effect on financial performance, the and insignificant effect on financial performance, the leverage variable has a positive and significant. Positive and significant effect on financial performance, and the variable board of commissioners, independent commissioners, company size has a negative and insignificant effect on financial performance. Commissioners, independent commissioners, company size and leverage simultaneously have an influence on financial performance